All-in-one high energy sorghum silage compared with and without antibiotic and conventional high energy sorghum silage for feedlot steers - Smart, L.I.; Drake, C.L. (Kansas State University. Agricultural Experiment Station, 2011)
Research done here in 1967 and 1968 indicated that adding a complete supplement to forage as it was ensiled gave results equal to using soybean meal at the time of feeding. The research continued to improve the complete silage. Previous work indicated that low levels of antibiotics increased bacterial growth and improved cellulose digestion in vitro. Therefore, two levels of antibiotics were tested in all-in-one silage ensiled and fed during 1968 and 1969.
Keywords: Beef; High energy; Sorghum silage; Feedlot steers; In Vitro